Class‐Specific Histone/Protein Deacetylase Inhibition Protects Against Renal Ischemia Reperfusion Injury and Fibrosis Formation. Issue 4 (23rd February 2015) - Levine, M. H.; Wang, Z.; Bhatti, T. R.; Wang, Y.; Aufhauser, D. D.; McNeal, S.; Liu, Y.; Cheraghlou, S.; Han, R.; Wang, L.; Hancock, W. W.
ABSTRACT: Renal ischemia‐reperfusion injury (IRI) is a common cause of renal dysfunction and renal failure. Histone/protein deacetylases (HDACs) regulate gene accessibility and higher order protein structures and may alter cellular responses to a variety of stresses. We investigated whether use of pan‐ and class‐specific HDAC inhibitors (HDACi) could improve IRI tolerance in the kidney. Using a model of unilateral renal IRI, we investigated early renal function after IRI, and calculated fibrosis after IRI using an automated scoring system. We found that pan‐HDAC inhibition using trichostatin (TSA) yielded significant renal functional benefit at 24–96 hours (p < 0.001). Treated mice developed significantly less fibrosis at 30 days (p < 0.0004). Class I HDAC inhibition with MS‐275 yielded similar effects. Protection from fibrosis formation was also noted in a cold ischemia transplant model (p < 0.008) with a trend toward improved cold ischemic survival in TSA‐treated mice. These effects were not accompanied by induction of typical ischemic tolerance pathways or by priming of heat shock protein expression. In fact, heat shock protein 70 deletion or overexpression did not alter renal ischemia tolerance. Micro‐RNA 21, known to be enhanced in vitro in renal tubular cells that survive stress, was enhanced by treatment with HDACi, pointing to possible mechanism. Abstract : The authors find that pan‐ and class I–specific histone deacetylase inhibitor administration prior to renal ischemia reperfusion injury leads to preservation of renal function and mitigation of fibrosis formation in both murine warm ischemia and cold ischemia isograft transplant models.